PHYSICAL PROPERTIES OF WOOD Pinus caribaea var. caribaea, Pinus caribaea var. hondurensis AND Pinus oocarpa FOR PENCIL PRODUCTION - Loiola, Pedro Lício; Klitze, Ricardo Jorge; Rocha, Márcio Pereira; Vidaurre, Graziela Baptista (Floresta, 2021)
The behavior of the physical properties of wood is important for its use in the industrial sector. Manufacturing for pencil production requires raw material with low specific mass and high dimensional stability. The objective of this study was to evaluate the properties of the physical specific basic mass properties, anhydrous and green, as well as the retractability of the 14 years old Pinus caribaea var. caribaea, 25 years old Pinus caribaea var. hondurensis and 35 years old Pinus oocarpa in the medulla sense of the bark, base and top of the trees. All species come from the Brazilian Cerrado region afforestation. As for dimensional stability, the Pinus caribaea var. caribaea and Pinus oocarpa had similar behaviors to the volumetric contraction, when evaluating the coefficient of anisotropy of wood species of Pinus caribaea var. caribaea had higher values of anisotropy coefficient, however, all tropical pine studied, qualify as a raw material for the pencil industry, being an alternative species traditionally used.